2019
DOI: 10.5539/ijms.v11n1p150
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Smokers' Behaviors After a 100% Tax Increase

Abstract: The aim of this study was to explore smokers' responses to a 100% tax increase on tobacco prices in Saudi Arabia. According to the World Health Organisation, an increase in tax is the single most effective tool to reduce the incidence of smoking. However, using a tax increase in other health areas (especially in reducing alcohol, sugar, or fat consumption) shows that consumers' reactions can differ according to socio-demographic characteristics. 334 participants of different generational cohorts and incomes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…It was also found that most of the participants started smoking from the age of 18 years. Alqarni 15 also had determined that most people acquire the habit of smoking during adolescence. As per the current analysis, there is a significant association between the number of cigarettes consumed in a day and the intention to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that most of the participants started smoking from the age of 18 years. Alqarni 15 also had determined that most people acquire the habit of smoking during adolescence. As per the current analysis, there is a significant association between the number of cigarettes consumed in a day and the intention to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The current price of a packet of cigarettes, 25.1 SAR (6.69 USD) is considered low according to two evaluations conducted in Saudi Arabia in 2019 and 2020. 34 , 37 By comparison, the price per pack (in US$) was $12.37 in the United Kingdom, $9.39 in France, $9.15 in Canada in 2018, 20 and $6.86 in the United States (US) in 2013. The US is the fourth largest tobacco producing country in the world, according to the Centers for Disease Control in the US.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO recommends that the excise tax be equivalent to 70% of the total price of the cigarette sale price. 18 , 37 In addition, growth in real individual income must be taken into account in order to minimize individual affordability to purchase cigarettes. 18 Regular pricing adjustments through specific excise levies will allow the government to create tailored anti-tobacco price and tax regimes that will improve the efficiency of national smoking curtailment practices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Saudi Arabia ratified the Framework Convention on Tobacco Control and enforced a tobacco taxation policy in the second quarter of 2017, with a total tax of 100% (16,17). However, only a few studies have been conducted to evaluate how taxation affects smoking habits demonstrating the effect of policies promoted by such a program (15,(18)(19)(20); this is due to the lack of adequate empirical research on the effect of tobacco taxes on smoking cessation in the Saudi Arabian context. Nevertheless, such studies have been conducted in other parts of the world (especially in the developed Western World).…”
Section: Relative Effectiveness Of Tobacco Taxationmentioning
confidence: 99%